Pengaruh Citra Destinasi, Harga, Tempat, dan Aksesibilitas Terhadap Minat Berkunjung Wisatawan Ke Museum Mulawarman Tenggarong - Sabran, Sabran; Iskandar, Iskandar; Palinggi, Yonathan; S, Syahruddin; Noryana, Noryana (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
The Mulawarman Museum is an important cultural and historical destination, housing the rich heritage of the Kutai Kartanegara Ing Martadipura Kingdom. This study aims to determine the influence of destination image, price, location, and accessibility on tourist visit interest, partially and to determine the most dominant variable. The urgency of this research is to maintain the momentum of increasing and even multiplying visitor interest with a more targeted approach. Destination image significantly influences tourist visit interest to the Tenggarong Museum. The hypothesis is accepted and proven true. Price does not significantly influence tourist visit interest to the Tenggarong Mulawarman Museum. The hypothesis is rejected and proven true. Location does not significantly influence tourist visit interest to the Tenggarong Mulawarman Museum. The hypothesis is rejected and not proven true. Accessibility significantly influences tourist visit interest to the Tenggarong Mulawarman Museum. The hypothesis is accepted and proven true. Accessibility is the most dominant variable and has the greatest influence among the other variables. The hypothesis is accepted and proven true.